Roflumilast: A Review of Chronic Obstructive Pulmonary Disease (COPD) Treatment - Ita Octafia; Dwi Octamy Sari; Novi Wulandari; Sandra Annisa; Linda Wahyuni Wongkar; Ferdias Kurnia Bahari; Faiz Farikhah; Moh Firmansah; Erfin Midhiawati; Fauna Herawati (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
Abstract Chronic Obstructive Pulmonary Disease (COPD) is a chronic airway inflammation with resulting progressive airflow limitation that has a high incidence, morbidity, and mortality. Roflumilast is an oral phosphodiesterase-4 inhibitor as a therapy to decrease the risk of COPD exacerbations in patients with moderate-severe COPD with a history of chronic bronchitis. Roflumilast can be given orally once daily as a single or combination drug. It can be used as COPD moderate-severe but also more beneficial as COPD mild treatment. The efficacy of Roflumilast can prevent exacerbations of repetition and can fixed lung function both in terms of FEV1 and vital capacity to force. The incidence of side effects, which are diarrhea and digestive disorders. The cost-effectiveness showed that Quality of life patient with Roflumilast is better than the group without additional. This paper aimed to review systematically Roflumilast as COPD treatment for the clinical application.Keywords                   : COPD, Roflumilast, phosphodiesterase-4 inhibitorCorrespondence          : fauna@staff.ubaya.ac.id